2022
DOI: 10.1021/acs.inorgchem.2c03773
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Photosynthesis of Cubic Fe@Fe3O4 Core–Shell Nanoparticle Well-Dispersed in N-Doping Carbonaceous Polymer Using a Molecular Dinitrosyl Iron Precursor

Abstract: Nanoscale zerovalent iron (NZVI) features potential application to biomedicine, (electro-/photo)catalysis, and environmental remediation. However, multiple-synthetic steps and limited ZVI content prompt the development of a novel strategy for efficient preparation of NZVI composites. Herein, a dinitrosyl iron complex [(N 3 MDA)Fe(NO) 2 ] (1-N 3 MDA) was explored as a molecular precursor for one-pot photosynthesis of a cubic Fe@Fe 3 O 4 core−shell nanoparticle (ZVI% = 60%) well-dispersed in an N-doping carbonac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(20 citation statements)
references
References 55 publications
(60 reference statements)
5
15
0
Order By: Relevance
“…High-resolution TEM (HRTEM) imaging revealed the core–shell structure of Fe@Fe 3 O 4 , with a shell thickness of approximately 4 nm. The HRTEM image displayed a d -spacing of 0.26 nm in the shell, corresponding to the (311) plane of the Fe 3 O 4 phase, and a d -spacing of 0.22 nm in the core, matching the (110) plane of Fe 0 (Figure d) . The TEM–selected area electron diffraction (TEM–SAED) pattern corroborated the PXRD results, showing the presence of the (110), (200), and (211) planes for the zerovalent iron phase as well as the (311) plane for Fe 3 O 4 (Figure e) .…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…High-resolution TEM (HRTEM) imaging revealed the core–shell structure of Fe@Fe 3 O 4 , with a shell thickness of approximately 4 nm. The HRTEM image displayed a d -spacing of 0.26 nm in the shell, corresponding to the (311) plane of the Fe 3 O 4 phase, and a d -spacing of 0.22 nm in the core, matching the (110) plane of Fe 0 (Figure d) . The TEM–selected area electron diffraction (TEM–SAED) pattern corroborated the PXRD results, showing the presence of the (110), (200), and (211) planes for the zerovalent iron phase as well as the (311) plane for Fe 3 O 4 (Figure e) .…”
Section: Resultssupporting
confidence: 60%
“…These images revealed that the Fe@Fe 3 O 4 exhibited a cube-like shape with an average size of 80 nm and were dispersed on an organic support. Transmission electron microscopy (TEM) analysis confirmed the SEM observations and demonstrated that the Fe@Fe 3 O 4 were well dispersed on the organic support (Figure c) . High-resolution TEM (HRTEM) imaging revealed the core–shell structure of Fe@Fe 3 O 4 , with a shell thickness of approximately 4 nm.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations